Meningkatkan Hasil Belajar PAKBP Materi Peran Roh Kudus dan Allah Tritunggal dengan Model PBL Fase E Kelas X di SMK Negeri 1 Sekadau - Florensius Arintia Kristanto; Nerita Setiyaningtiyas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2025)
This study aims to improve student learning outcomes at SMK Negeri 1 Sekadau through the application of the PBL (Problem Based Learning) learning model. The background of this study is based on the low level of student learning motivation with the usual model, this is indicated by low participation and motivation in understanding concepts. The PBL model was chosen because it is able to encourage students to participate critically, analytically in solving problems. This study was conducted for two cycles with the research process: planning actions, implementing actions in cycle I and cycle II, conducting observations during the learning process in two cycles, conducting evaluations at the end of each cycle, analyzing evaluation data and observation results and conducting reflections based on the results of the analysis and student responses. The results of this study indicate that the value of increasing student learning outcomes starting from cycle I 71.43% and Cycle II 96.43%. meaning there is an increase in learning. Thus, the results of this study can be obtained a picture that the Application of the Problem Based Learning Learning Model as an effort to improve the learning outcomes of class X students of SMKN 1 Sekadau in the Catholic Religious Education dan Moral subject can be improved by using the application of the Problem Based Learning learning model.